Perancangan Komunikasi Visual Sunnah dalam Adab Berpakaian untuk Anak - Aryadwipa Angesti Faradhiga (Institut Seni Indonesia Yogyakarta, 2019)
Abstract.Islam is a religion known as a doctrine of belief that contains various kinds of command and prohibitions in its inside,one of that is the command that directs about courtesy in a dressing. The general function of clothing is to cover body parts that forbidden to seen or in other words called aurat.But in practice, not yet all Moslem apply and obey the law/shari'ah well and correctly, especially in Indonesia.This design persuades the target audience, namely children and parents to jointly agree on guidelines for applying the sunnah rules that are conveyed. The design method is implementing Tim Brown's design thinking approach that useful for combining the results of analysis and creative ideas. The method of design thinking approach consists of five stages, empathize, define, ideate, prototype, and test. Data analysis uses a 5W + 1H approach to determine design goals, target audience, and problem-solving methods.The book designing is entitled‘Mengenal Sunnah dalam Adab Berpakaian’applying descriptive story approaches to convey its message.The visual message is conveyed through character design consisting of the character of boys and girls.Illustration and layout done by rough sketch, and then visualised into digital.Supporting media used such as pins and posters.Keywords: Children’s book, illustration book, sunnah of dressingRelevance to Visual Comunication Design Practice: As a reference and alternative visual communication design solutions for designers and researchers, for academic or practical needs.